Molecular and cellular therapies for motor neuron diseases - Boulis, Nicholas; O'Connor, Deirdre (Deirdre M.); Donsante, Anthony (ClinicalKey., 2017)
"Molecular and Cellular Therapies for Motor Neuron Diseases discusses the basics of the diseases, also covering advances in research and clinical trials. The book provides a resource for students that will help them learn the basics in a detailed manner that is required for scientists and clinicians. Users will find a comprehensive overview of the background of Amyotrophic Lateral Sclerosis (ALS/Lou Gehrig's Disease) and Spinal Muscular Atrophy (SMA), along with the current understanding of their genetics and mechanisms. In addition, the book details gene and cell therapies that have been developed and their translation to clinical trials"--Publisher's description